Status of Novel Cardiovascular Risk Factor and Cardiovascular Disease Risk in an Urban Cuban PopulationA Pilot Study (Journal of Health, Population and Nutrition, 2011)
Cardiovascular disease is the main cause of death in Cuba, yet the prevalence of novel risk factors is not known. To examine the prevalence of risk factors of traditional and novel cardiovascular diseases (CVDs) among an urban Cuban population, a cross-sectional pilot survey was undertaken in Havana city, Cuba. Ninety-seven adults aged 45-60 years registered to receive medical care at a policlinic. The prevalences of rates of CVD risk factors were: hypertension (≥140/90 mmHg) (53.6%), hypercholesterolaemia (total cholesterol >5.2 mmol/L) (47.0%), low high-density lipoprotein (HDL)-cholesterol (